2020
DOI: 10.2147/opth.s276120
|View full text |Cite
|
Sign up to set email alerts
|

<p>Visual Acuity, Defocus Curve, Reading Speed and Patient Satisfaction with a Combined Extended Depth of Focus Intraocular Lens and Multifocal Intraocular Lens Modality</p>

Abstract: Purpose To evaluate the vision, defocus curve, reading speed and patient satisfaction after implantation of an extended depth of focus (EDOF) IOL in one eye and a diffractive multifocal in the fellow eye. Setting One clinical practice in the USA. Design Prospective unmasked non-randomized clinical trial. Methods Subjects presenting for routine cataract surgery interested in reducing their dependence on spectacles w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…The binocular defocus curve result of the current study showed a flat peak around 0.00 logMAR between 0.0 and +0.5 D power, followed by a flat intermediate visual acuity zone around 0.10 logMAR between −1.0 and −2.0 D power, ending with a narrow near visual cuity zone around 0.15 – 0.20 logMAR between −2.5 and −3.0 D power. The dip point around 0.10 – 0.15 logMAR in −0.5 D power gives the defocus curve an appearance similar to previously reported defocus curves of multifocal IOLs including Alcon PanOptix and Zeiss AT LISA lenses, 18,25,33,34 depicting a slightly worse continuous visual acuity performance that was provided by EDOF IOLs. 11,28 Interestingly, the defocus curve shows a good performance that is above 0.10 logMAR units between 0.0 and +1.0 D power, therefore a postoperative myopic refractive “surprise” might be well tolerated.…”
Section: Discussionsupporting
confidence: 84%
“…The binocular defocus curve result of the current study showed a flat peak around 0.00 logMAR between 0.0 and +0.5 D power, followed by a flat intermediate visual acuity zone around 0.10 logMAR between −1.0 and −2.0 D power, ending with a narrow near visual cuity zone around 0.15 – 0.20 logMAR between −2.5 and −3.0 D power. The dip point around 0.10 – 0.15 logMAR in −0.5 D power gives the defocus curve an appearance similar to previously reported defocus curves of multifocal IOLs including Alcon PanOptix and Zeiss AT LISA lenses, 18,25,33,34 depicting a slightly worse continuous visual acuity performance that was provided by EDOF IOLs. 11,28 Interestingly, the defocus curve shows a good performance that is above 0.10 logMAR units between 0.0 and +1.0 D power, therefore a postoperative myopic refractive “surprise” might be well tolerated.…”
Section: Discussionsupporting
confidence: 84%
“…Comparative analysis has shown that ZFR00V had slightly better far-to-intermediate range of vision against TFNT00. The dip point around 0.10–0.15 logMAR in −0.5 D power for ZFR00V IOL was found comparable to TFNT00 IOL, giving an appearance of a multifocal IOL defocus curve similar to previously reported defocus curves for TFNT00 and Zeiss AT LISA lenses, 18,25,32,33 depicting a slightly worse continuous visual acuity performance that was provided by EDOF IOLs. 11,28 The defocus pattern of the current study had similarities with the study held by Ribeiro et al which showed mean visual acuity above 0.10 LogMAR between + 0.50 D and −3.00 D. 31 ZFR00V lens showed a good performance between 0.0 and + 1.0 D powers which was above 0.10 logMAR units, therefore targeting a slight postoperative myopic refractive target might be advisable to further enhance continuous far-to-intermediate vision.…”
Section: Discussionsupporting
confidence: 79%
“…Some surgeons will use a combination of these approaches. 1,2 The multifocal IOLs, particularly the trifocals, generally provide the highest likelihood of complete spectacle independence. [3][4][5] EDOF lenses are likely to provide good vision at distance and intermediate, with slightly worse near vision, but the expectation is that visual disturbances will be lower with an EDOF IOL because there are not two (or three) distinct foci.…”
Section: Introductionmentioning
confidence: 99%